2016
DOI: 10.1515/biolog-2016-0149
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and precipitation effects on breeding productivity of some passerines — a multivariate analysis of constant effort mist-netting data

Abstract: The relationship between the temperature, the precipitation of the breeding season’s months, and the annual proportions of the first year birds such as the indicators of the breeding success were examined by canonical correspondence analysis (CCA) having targeted nine common passerine species. The results of our study have shown that the high April and May temperature has been favourable for the breeding of the partial and the short-distance migrants, the common blackbird

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…Ambient temperature and precipitation do not only affect survival of nestlings, they can have a complex interacting impact on different age classes, e.g. recruitment of fledglings (Öberg et al , Gyurácz et al ) or parental survival (Öberg et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Ambient temperature and precipitation do not only affect survival of nestlings, they can have a complex interacting impact on different age classes, e.g. recruitment of fledglings (Öberg et al , Gyurácz et al ) or parental survival (Öberg et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Our annual captures also suggest stabile populations in this western Hungarian study site (Tömörd) for both tit species. The results of an earlier study showed that high temperatures in the breeding season was the key determinant of increased annual captures of first-year birds of some short-distance migrants (Gyurácz et al 2016). The increasing and stable populations of forest tit species is most likely due to the expanding forested area of Hungary.…”
Section: Discussionmentioning
confidence: 96%
“…As part of a long-term monitoring study to understand passerines' population dynamics and migration (Gyurácz & Bánhidi 2008, Lukács et al 2015), here we report annual capture-recapture data, and estimate age-and sex-specific survival for one Palearctic and one European cavity-nesting and partial-migrant species of tits: Blue Tit Cyanistes caeruleus and Great Tit Parus major breed and migrate sympatrically in western Hungary (Gyurácz et al 2017). The European breeding populations of Great Tit and Blue Tit appear to have increased moderately in recent decades (PECBMS 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we calibrated individual-based models (IBMs) that explictly include crucial processes such as density-dependence and climatic impacts on demographic rates [9]. To describe the climate, we used precipitation in addition to temperature as predictive variables [49]. When comparing our spatiotemporal predictions against observations, our models achieved acceptable to excellent predictive accuracy, with the highest performance for the alpine accentor.…”
Section: Discussionmentioning
confidence: 99%